Financial Management among Couples in Long-Distance Marriage - Khairatun Hisan; Ajran Nura; Fahriansah; Shelly Midesia (Jurnal Investasi Islam, 2025)
This study aims to explore family financial management among couples in a Long Distance Marriage (LDM). The research uses a descriptive qualitative approach, with primary data collected through interviews, surveys, and observation. Informants include lecturers from IAIN Langsa undergoing LDM, selected via snowball sampling. Data were analyzed using Miles and Huberman’s qualitative analysis model, which includes data reduction, data presentation, and conclusion drawing. The findings reveal that financial management in LDM couples varies depending on the division of roles between husband and wife, with most husbands entrusting financial management to their wives. Savings, investments, debts, and emergency funds/insurance are key components in ensuring financial well-being. This study emphasizes the importance of wise financial management in navigating the challenges of distance and differing roles within LDM families.